Effects of aldosterone and potassium-sparing diuretics on electrical potential differences across the distal nephron. - Gross, J B (1977)
We have previously shown that the transtubular potential of the rabbit cortical collecting tubule varies in concert with changes in plasma mineralocorticoid levels, while the potential of the distal convoluted tubule is invariant with such changes. In the present studies we have examined the effects of in vitro addition of d-aldosterone to isolated tubules, as well as the effects of triamterene and spirolactone. d-Aldosterone (0.2 mum added to the perfusate or 1 muM added to the bathing medium) resulted in a marked stimulation of the transtubular potential difference (lumen-negative) after a short latent period. d-Aldosterone had no effect on the potential difference of distal convoluted tubules of intact or adrenalectomized rabbits. Both the magnitude of the response and the length of the latent period in the cortical collecting tubule after aldosterone were markedly temperature-dependent. Triamterene caused a gradual but reversible inhibition of the potential difference in the cortical collecting tubule but had no effect in the distal tubule. Spirolactone, when added before aldosterone, blocked the electrical response to the hormone in the cortical collecting tubule, and produced a gradual inhibition of the potential difference in mineralocorticoid-stimulated tubules. Spirolactone had no effect on the potential difference of the distal tubule. We conclude that (a) the influence of aldosterone on the potential across the distal nephron is restricted to the distal convoluted tubule, (b) the electrical response to aldosterone and the latent period are temperature-dependent, (c) the response to aldosterone is blocked by spirolactone, and (d) triamterene inhibits the potential difference only in the cortical collecting tubule.